(untitled) (Numerus academy review, 2026)
Today, electronic advertisement has taken a large part in the means of electronic communication, which pushed the Algerian legislator to reform its provisions via Law no. 18-05 which is related to electronic commerce. Due to what it offers and its effectiveness, especially in commercial transactions and coping more with the global epidemic situation of Covid-19. Yet owing to the increase of the electronic means of communication, infringements were recorded regarding electronic advertisement, as well as misleading and false publicity have appeared and spread, which endanger the electronic consumer. This research paper aims to know the effectiveness of electronic advertisement and the impact of deceptive advertising on commercial transactions, and the position of the Algerian legislator on that, by extrapolating the laws and codes that were written to regulate and control this new type of transactions.